Renal tuberculosis mimicking xanthogranulomatous pyelonephritis: ultrasonography, computed tomography and magnetic resonance imaging findings - İzbudak Öznur, İzlem; Sözen, Sinan; Işık, Sedat (The Turkish Journal of Pediatrics, 2002)
The incidence of tuberculosis has been increasing in recent years, and its treatment has also become challenging. The diagnosis of renal tuberculosis is often difficult and delayed. Early and correct diagnosis of tuberculosis with different organ system involvement is very important and can be easier with ultrasonography, computed tomography and/or magnetic resonance imaging. Although renal tuberculosis is the result of hematogenous spread more commonly from the lungs, less than 5%, of patients with urinary tract tuberculosis have active pulmonary disease.Renal tuberculosis may show variable radiological findings depending on the stage of the infection. Although an end-stage "autonephrectomized" kidney in tuberculosis is classically defined to be small in size, enlargement may on rare occasions be observed, which is the case in our patient. This form greatly mimics diffuse xanthogranulomatous pyelonephritis. Both diseases show thickening of the perirenal fasciae and spread of inflammation into the adjacent organs. Computed tomography and magnetic resonance imaging may show some specific features to differentiate these two entities.
Keywords: kidney; tuberculosis; xanthogranulomatous pyelonephritis; ultrasound; computed tomography; magnetic resonance imaging